A lateral electrophoretic flow diagnostic assay1. Issue 6 (21st March 2015) - Lin, Robert; Skandarajah, Arunan; Gerver, Rachel E.; Neira, Hector D.; Fletcher, Daniel A.; Herr, Amy E.
<x xml:space="preserve">Abstract</x> Antibodies against the hepatitis C virus are detected in human sera using the CellScope-enabled electrophoretic barcode assay.